2014
DOI: 10.1107/s2053230x14002519
|View full text |Cite
|
Sign up to set email alerts
|

A 2.2 Å resolution structure of the USP7 catalytic domain in a new space group elaborates upon structural rearrangements resulting from ubiquitin binding

Abstract: A sparse-matrix screen for new crystallization conditions for the USP7 catalytic domain (USP7 CD ) led to the identification of a condition in which crystals grow reproducibly in 24-48 h. Variation of the halide metal, growth temperature and seed-stock concentration resulted in a shift in space group from P2 1 with two molecules in the asymmetric unit to C2 with one molecule in the asymmetric unit. Representative structures from each space group were determined to 2.2 Å resolution and these structures support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
2
33
1
Order By: Relevance
“…In the USP7-ubiquitin complex structure (PDB code: 1NBF), we found that the same narrow pocket was occupied by the ubiquitin C- terminus (Supplementary Figure S3). These results suggest that the inhibition mechanism of CDDO-Me may be explained by its displacement of the ubiquitin C terminus while binding with USP7 [2526]. However, further experimental data, such as crystal structures, are necessary to confirm this docking hypothesis.…”
Section: Resultsmentioning
confidence: 97%
“…In the USP7-ubiquitin complex structure (PDB code: 1NBF), we found that the same narrow pocket was occupied by the ubiquitin C- terminus (Supplementary Figure S3). These results suggest that the inhibition mechanism of CDDO-Me may be explained by its displacement of the ubiquitin C terminus while binding with USP7 [2526]. However, further experimental data, such as crystal structures, are necessary to confirm this docking hypothesis.…”
Section: Resultsmentioning
confidence: 97%
“…The majority of USP catalytic domain structures available to date were determined in complex with either ubiquitin or a covalent inhibitor including USP2 ( 28 ), USP4 ( 24 ), USP5 ( 29 ), USP7 ( 30 ), USP12 ( 31 ), USP18 ( 32 ), USP14 ( 33 ), USP21 ( 34 ), USP30 ( 35 ), USP46 ( 36 ), and CYLD ( 37 ). Structures that do not have a ligand or ubiquitin covalently bound to the catalytic cysteine are available for USP7 (PDB codes 1NB8 , 2F1Z , 4M5X ( 30 , 38 , 39 )), USP14 (PDB code 2AYN ( 33 )), CYLD (PDB code 2VHF ( 40 )), USP8 (PDB code 2GFO ( 27 )), USP18 (PDB code 5CHT ( 32 )), and USP12 (PDB codes 5K1B and 5K16 ( 41 )). Among the latter structures, the USP15 catalytic core is most closely related to USP8 (46% sequence identity) followed by USP12 (26.32% sequence identity), whereas it is more distantly related to USP7 (21.99% sequence identity), USP14 (19.94% sequence identity), and CYLD (11.8% sequence identity).…”
Section: Resultsmentioning
confidence: 99%
“… Comparison with other USP catalytic core structures determined in the absence of ubiquitin. A , crystal structures of USP15 ( blue ) and USP4 (PDB code 2Y6E ( 24 )), USP8 (PDB code 2GFO ( 27 ), USP7 (PDB code 4M5X ( 38 )), USP14 (PDB code 2AYN ( 33 )), and USP12 (PDB code 5K16 ( 41 )) shown in a gray cartoon representation with catalytic triad residues highlighted in green and BL1, SL, and BL2 loop regions each depicted in red. B , superposition of the same structures as seen in A , highlighting the most variable regions in the structures.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic domain of USP7 constitutes a well characterized hand like architecture with finger, palm and thumb that is mainly responsible for its catalytic activity. The coordinates for catalytic domain were obtained from PDB-ID 4M5W [ 25 ]. From literature, we found that auxiliary domains are essential for biological function, therefore PDB-ID 5FWI [ 26 ] that contains CD, CH and also three additional domains as UBL123 was also used.…”
Section: Resultsmentioning
confidence: 99%
“…Crystals 4M5W (APO) [ 25 ] and 5FWI (APO) [ 26 ] were obtained from Protein Data Bank The missing residues in 4M5W (L505-R508) and 5FWI (D459-N460 (BL2) and D502-H509) were interpolated by using PLOP algorithm [ 37 ] implemented in Schrodinger suite and the optimum conformation of loop was chosen on the basis of lowest energy. The loop conformations were optimized and then both the structures were minimized.…”
Section: Methodsmentioning
confidence: 99%